(untitled) (Itinera, 2017)
Traditionnally, live shows construct their spectators’ political consciousness through intellectual means. Taking George Tabori’s play Mein Kampf (Farce) (1987), Roberto Cossa’s La Nonna (1990), and Les Sept doigts de la main circus company’ show Cuisine et confessions (2014) as examples, this paper explores how the use of taste can also serve the same purpose. It demonstrates how the sense of taste is not necessarily antagonistic to « sense » as good understanding and judgement, and that it is notably through the transformation taste brings about in the relationship between stage and spectator time that both are reconciled.